Applicability of GPR and a rebar detector to obtain rebar information of existing concrete structures. (December 2019) - Rathod, Harsh; Debeck, Scott; Gupta, Rishi; Chow, Brian
Abstract: Much of Canada's existing infrastructure was constructed during 1950s, 1960s and 1970s. These include all transportation infrastructures such as bridges, highways, tunnels, etc. It is important to know the condition of these aging infrastructures in terms of their load carrying capacity to ensure their safety and serviceability. There are several old reinforced concrete slab bridges within the network of Ministry of Forests in B.C. Canada that have unknown rebar spacing, cover and diameter. This research paper discusses the application of Ground Penetrating Radar (GPR) and a Rebar detector in obtaining valuable information about rebar diameter, spacing and cover depth required to determine the structural capacity (load rating) of bridge decks. For this, GPR and the rebar detector have been applied on an existing bridge deck, a precast bridge girder and a reinforced concrete test slab panel available in the materials lab at the Facility for Innovative Materials and Infrastructure Monitoring (FIMIM) at the University of Victoria (UVic). To assess the applicability of GPR and Profoscope (Rebar Detector) in obtaining rebar information, the results obtained using both the techniques were compared in terms of their errors in determining all three parameters of rebar; diameter, spacing and cover depth. The results were validated by measuring the actual diameter, spacing and cover depth of the rebar in the reinforced concrete test slab available in the lab at UVic.